(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This work introduces the concept of bipolar fuzzy soft Boolean rings (BFSBRs), an algebraic structure that unifies soft sets (SSs) and bipolar fuzzy sets (BFSs) within Boolean ring (BR) systems. It develops essential definitions, operations, and properties for modeling dual-sided uncertainty in decision-making contexts. Beyond its theoretical contributions, the framework is designed to support early-stage mathematical research by science classroom students. It encourages deeper engagement with abstract mathematical thinking and fosters collaboration between students, teachers, and research mentors, thus promoting a more inclusive and research-oriented learning environment.